SUBSTANTIVE V EXCEPTION PROVISION DALAM GATT: STUDI KASUS INDONESIA DI WTO - Suri, Jessica Priscilla (Collegium Studiosum Journal, 2023)
This research delves into the dynamic interplay between substantive provisions and exception clauses within the General Agreement on Tariffs and Trade (GATT). Focusing on the case of Indonesia in the World Trade Organization (WTO), the study employs a comprehensive methodology involving legal analysis and a case study approach. Through this investigation, the research aims to unravel the intricate implications of substantive versus exception provisions in the context of international trade agreements.